2019
DOI: 10.1038/s41598-019-52043-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Effect of Nitrogen Supply for Soybean at the Beginning Flowering Stage on Biomass and Sucrose Metabolism

Abstract: Nitrogen application at the beginning flowering stage (R1 stage) increased the soybean grain yield, however, the rapid effect of enriched nitrogen at R1 growth stage on soybean dry matter accumulation and sugar metabolism is still unclear. Continuous high nitrogen (CHN), Continuous low nitrogen (CLN), Enriched nitrogen supply at R1 stage (ENS) treatments were applied on two soybean cultivars (Liaodou11, Liaodou14), to investigate the effect of enriched nitrogen on plant biomass accumulation and sucrose metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…These results reflect the differences in N functions for SG production at different growth stages. Thus, the accumulated N during the early growth stage is mainly functioned in plant growth and biomass formation, while the N after the vegetative growth stage should consider the leaf secondary metabolism (Khan et al 2020;Zhou et al 2019b). Collectively, as plant growth processes, the contribution of stevia biomass to TSG yield decreases, which is the opposite trend as the contribution of SG concentrations.…”
Section: N and Tsg Accumulation At Different Growth Stagesmentioning
confidence: 99%
“…These results reflect the differences in N functions for SG production at different growth stages. Thus, the accumulated N during the early growth stage is mainly functioned in plant growth and biomass formation, while the N after the vegetative growth stage should consider the leaf secondary metabolism (Khan et al 2020;Zhou et al 2019b). Collectively, as plant growth processes, the contribution of stevia biomass to TSG yield decreases, which is the opposite trend as the contribution of SG concentrations.…”
Section: N and Tsg Accumulation At Different Growth Stagesmentioning
confidence: 99%
“…Nutrition competition among sourced and sink organs caused flowers and pod abortion and abscission, decreasing soybean pod number and grain yield ( Raza et al, 2020 ). Nitrogen application at the R1 stage increased the soybean grain yield by promoting biomass accumulation during the soybean reproductive growth stage ( Zhou H. et al, 2019 ). Similarly, results in this experiment showed that the DA-6 significantly ( p < 0.05) increased the soybean aboveground dry matter ( Figure 5 ), and the yield and yield components of soybean ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a legume crop, soybean could convert atmospheric nitrogen into biological ammonium with the help of symbiotic bacteria in root nodules by biological nitrogen fixation (Zhou et al, 2019). And the soybean nodule number and nodule weight were important phenotype indicators that reflect the ability of root nodules on biological nitrogen fixation.…”
Section: Soybean Nodule Phenotype and The Sucrose And Starch Metabolismmentioning
confidence: 99%